PENGARUH KUALITAS PELAYANAN DAN E-SERVICE QUALITY TERHADAP LOYALITAS PELANGGAN DIMEDIASI KEPUASAN PELANGGAN PADA KONSUMEN ELHA TRANS INDRAPURA - Hafis, Zuraizul; Mohammad Andriansyah; Rakhmawati Purba; Indra Welly Arifin (Cattleya Darmaya Fortuna, 2025)
This study aims to determine the influence of service quality and e-service quality on customer loyalty mediated by customer satisfaction in ELHA TRANS INDRAPURA consumers. The research method used is a quantitative method using SmartPLS version 3.0. The questionnaire was distributed to 96 respondents. The data analysis methods used in the study are measurement models (outer models), namely validity tests, reliability tests, then structural models (inner models) including: determination coefficient/r-square (r2) and hypothesis testing with t-statistical tests and indirect influence tests. The results of SmartPLS 3.0 in this study are that service quality affects customer satisfaction at ELHA TRANS INDRAPURA, e-service quality affects customer satisfaction at ELHA TRANS INDRAPURA, service quality does not affect customer loyalty at ELHA TRANS INDRAPURA, e-service quality affects customer loyalty at ELHA TRANS INDRAPURA, customer satisfaction does not affect customer loyalty at ELHA TRANS INDRAPURA, customer satisfaction does not affect customer loyalty at ELHA TRANS INDRAPURA, service quality has no effect on customer loyalty with customer satisfaction as an intervening variable in ELHA TRANS INDRAPURA consumers, and e-service quality has no effect on customer loyalty with customer satisfaction as an intervening variable in ELHA TRANS INDRAPURA consumers